Clinical Trials of Oncolytic Viruses in Breast Cancer - Carter, Mary E.; Koch, André; Lauer, Ulrich M.; Hartkopf, Andreas D. (Frontiers in Oncology, 2021)
Breast cancer is the second most common kind of cancer worldwide and oncolytic viruses may offer a new treatment approach. There are three different types of oncolytic viruses used in clinical trials; (i) oncolytic viruses with natural anti-neoplastic properties; (ii) oncolytic viruses designed for tumor-selective replication; (iii) oncolytic viruses modified to activate the immune system. Currently, fourteen different oncolytic viruses have been investigated in eighteen published clinical trials. These trials demonstrate that oncolytic viruses are well tolerated and safe for use in patients and display clinical activity. However, these trials mainly studied a small number of patients with different advanced tumors including some with breast cancer. Future trials should focus on breast cancer and investigate optimal routes of administration, occurrence of neutralizing antibodies, viral gene expression, combinations with other antineoplastic therapies, and identify subtypes that are particularly suitable for oncolytic virotherapy.